Computational fluid dynamics simulation of the supercritical carbon dioxide flow in beam dyeing. Issue 13 (July 2019) - Reji, RV; Raman, SK; Kim, TY; Kim, HD
The recent development in the technologies of supercritical carbon dioxide (S-CO2 ) has caused a remarkable change in the dyeing process in the textile industry. The conventional wet-dyeing process using water is being replaced with the dry-dyeing process using S-CO2 . The uniform addition of coloring material is necessary for any dyeing process. In the case of the beam dyeing process, an equal distribution of the dye fluid through the porous beam has to be ensured in order to achieve an evenly distributed dyeing. The present study focuses on the fluid dynamics aspects of the S-CO2 beam dyeing process in order to study the flow characteristics and thereby obtain performance improvement. Computational fluid dynamics analyses were carried out and the methodology is validated with experimental results from a previous study. The flow distribution of S-CO2 through a porous beam is analyzed at different conditions, such as varying the operating pressure, mass flow rate and inlet temperature. The comparison of compressible and incompressible flow through beam dyeing is also discussed. The current study revealed that the increase in mass flow rate through the system leads to higher non-uniformity in distribution. The operating pressure and inlet temperature were found to significantly affect the flow distribution. The flow reversal condition showed a mass flow distribution opposite to that of the normal flow condition. The cyclic flow condition with periodic normal and the reversed flow condition provide better uniformity in distribution of the flow than the normal flow condition. The present results provide guidelines to improve the levelness of the dye distribution in the fabric material.